2019
DOI: 10.3389/fnins.2019.00044
|View full text |Cite|
|
Sign up to set email alerts
|

Role of FOXO3 Activated by HIV-1 Tat in HIV-Associated Neurocognitive Disorder Neuronal Apoptosis

Abstract: There are numerous types of pathological changes in human immunodeficiency virus (HIV)-associated neurocognitive disorder (HAND), including apoptosis of neurons. HIV-1 transactivator of transcription (Tat) protein, which is encoded by HIV-1, may promote apoptosis in HAND. Forkhead box O3 (FOXO3) is a multispecific transcription factor that has roles in many biological processes, including cellular apoptosis. The aim of this study was to determine whether FOXO3 is activated by HIV-1 Tat and to investigate its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…A similar effect occurs with the viral protein Nef, which prevents autophagic maturation contributing to neurodegeneration [100]. In addition, Tat can induce neuronal apoptosis by activating forkhead box O3 (FOXO3), which is translocated to the nucleus through c-Jun N-terminal kinase (JNK) signaling to upregulate the expression of pro-apoptotic genes such as Bcl-2-like 11 (Bim) and downregulate anti-apoptotic factors such as B-cell lymphoma 2 (Bcl-2) [101].…”
Section: Cells Infected By Hiv-1 In the Cnsmentioning
confidence: 99%
“…A similar effect occurs with the viral protein Nef, which prevents autophagic maturation contributing to neurodegeneration [100]. In addition, Tat can induce neuronal apoptosis by activating forkhead box O3 (FOXO3), which is translocated to the nucleus through c-Jun N-terminal kinase (JNK) signaling to upregulate the expression of pro-apoptotic genes such as Bcl-2-like 11 (Bim) and downregulate anti-apoptotic factors such as B-cell lymphoma 2 (Bcl-2) [101].…”
Section: Cells Infected By Hiv-1 In the Cnsmentioning
confidence: 99%
“…These results may be attributed to the genes downstream of FoxO3a and related to apoptosis, including Bim, Fasl, TRAIL and Bcl. [38][39][40][41][42] In conclusion, our results found that FoxO3a plays an important role in the apoptosis, migration and invasion of HTR8-S/Vneo cells, which may be partially explained by its affinity to the ICAM1 promotor.…”
Section: Discussionmentioning
confidence: 55%
“…Replication of HIV and the release of viral proteins damage the functioning of neurons leading to their death. In particular, studies have reported about HIV Nef and Tat proteins wherein HIV viral protein Nef prevents autophagic maturation leading to neurodegeneration [ 84 ] while Tat protein activates forkhead box O3 (FOXO3) leading to induction of neuronal apoptosis [ 85 ]. Furthermore, it is reported by Kaul et al that HIV-1, as well as its structural proteins mainly envelope protein, interferes directly affecting biological functions of neural stem and progenitor cells via the receptor-ligand axis between CXCR4-SDF-1 causing neuronal injury followed by the death of existing neurons leading to the development of HAD.…”
Section: Type Of Cells Infected With Hiv In the Central Nervous System (Cns)mentioning
confidence: 99%